The impact of english for specific purposes (esp) methodology on the students' reading comprehension: Case of students of technical english II at the School of Chemistry and Pharmacy, University of El Salvador, semester II, year 2015. - Álvarez de Mangandi, Johanna Claribel
Effective English language education is essential around the world. Nowadays, many students want to learn English according to their needs. Indeed, Teaching English for Specific Purposes (ESP) is a practical discipline with the most important objective of helping students to leam. Therefore, this paper makes an attempt at making a study about the impact of English for Specific Purposes (ESP) methodology on the leamers' reading comprehension: Case of students of Technical English II at the School of Chemistry and Pharmacy, University of El Salvador, Semester II, year 2015, in order to present guidelines aimed at improving the students' learning process. This research is carried out because students require English teaching according to each study field and their needs. Indeed, teaching ESP is aimed at developing leamers' skills in English depending on the area of their professional field. It means that such teaching should be connected to students' specific (professional) demands. Therefore, the theory regarding ESP methodology should be compared or contrasted with reality as observed at the School of Chemistry and Pharmacy at the University of El Salvador. Indeed, the professors in charge of Technical English II can introduce changes or modifications to their methodology based upon the students' reactions to their class. These are the important reasons for conducting this research. This investigation is conducted with the interest not only in identifizing whether ESP methodology has a positive or negative impact on students' reading comprehension, but also in presenting guidelines aimed at improving the students' learning process.